Double hybrids of low in breeding depression corn in F2. - de León, Humberto (2016)
The first and second generations (F1 and F2) of 33 double hybrids of com were studied in order to evaluate grain yield decrease caused by generational advance, and to detect hybrids with a low inbreeding depression. Effects of in breeding depression were also evaluated according to flowering days (FD), plant height (PH), ear height (EH), root lodging (RL), and stem height (SH), bad coverage (BC), and roUen ears (RE). Doub1e hybrids with a high yield were obtained in F1, and without in breeding in F2 at arate of six to nine percent, depending on the evaluation environment, indicating insignificant in breeding effects.